(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
Software-Defined Networking (SDN) represents a major transition from traditional hardware-based networks to programmable software-based networks. While SDN brings visibility, elasticity, flexibility, and scalability, it also presents security challenges. This paper describes some of the hands-on labs we developed for teaching SDN security using the CloudLab platform. The hands-on labs have been used in a graduate level course on SDN/NFV related technologies. Our teaching experience of the hands-on labs is discussed. The hands-on labs can be adopted by other instructors to teach SDN security.